(untitled) (International relations and international law Journal, 2026)
This study examines the application of artificial intelligence in the analysis and resolution of ethnic conflicts, with particular emphasis on the specific features of intercultural communication in Central Asia. The study begins with an overview of the current state of ethnic conflicts in the region and identifies the main causes and problem areas associated with interethnic tensions. The primary aim of the research is to analyse the role of artificial intelligence in the collection and processing of conflict-related data. This approach makes it possible to identify hidden patterns and trends that may remain undetected when traditional analytical methods are used. The study provides a comprehensive examination of the potential of machine-learning and data-analysis algorithms to identify conflicts and optimise strategies for their resolution. In addition, the potential of machine learning and natural language processing technologies for interpreting intercultural communication and preventing the escalation of conflicts is explored in detail. The analysis of social media data and statements made by public opinion leaders using artificial intelligence algorithms makes it possible to respond promptly to changes in public sentiment and predict potential conflicts. The study also considers the development of decision-support systems based on machine-learning algorithms. Such systems can facilitate the formulation of conflict-management strategies by using predictive models and simulation-based approaches. Taking into account the cultural and social characteristics of the region, these systems can contribute to more effective and equitable decision-making. The proposed approach is aimed at identifying the specific features of conflicts and possible ways of resolving them through the analysis of multilingual texts. It also assesses the potential of machine learning to automate decision-making processes in complex intercultural contexts. The findings demonstrate the considerable potential of artificial intelligence for conflict resolution in Central Asia and highlight the need for further research in this field. Keywords: communication, clustering, sentiment analysis, conflict, analysis, culture, ethnicity, model.